Community Empowerment through the Covid Response Program in Sidoarjo Regency - Krisnawan, Gading Dwi; Agustina, Isna Fitria (Indonesian Journal of Public Policy Review, 2022)
This research is based on the background of a pandemic that has caused a drastic decline in the community's economy, this of course has an impact on many sectors. Community empowerment is a development capital with people's roots and is an effort to increase the dignity of some of our people who are trapped in poverty. This study aims to describe community empowerment through the COVID-19 response program at the Sidoarjo Regency Job Training Center and the obstacles faced in community empowerment through the COVID-19 response program at the Sidoarjo Regency Job Training Center. Qualitative descriptive research method, where data collection techniques are carried out by means of in-depth interviews, observation and documentation. The informants in this study were employees of the Sidoarjo Regency BLK and training participants at the Sidoarjo Regency BLK. At the capacity stage, namely the type of competency-based training provided by BLK Sidoarjo in the COVID-19 response program, it consisted of two trainings, namely welding to make sinks for washing hands and sewing to make faceshields, masks, and PPE. At the empowerment stage, the training participants are given incentives in the form of money at the end of the training which can be used as capital to buy tools to open a business.